By numerical results it follows that:

$$\int_0^1 \frac{H_t}{t}dt=\sum_{k=1}^{\infty} \frac{\ln (1+\frac{1}{k})}{k}=1.25774688694436963$$

Here $H_t$ is the harmonic number, which is the generalization of harmonic sum and has an integral representation:

$$H_t=\int_0^1 \frac{1-y^t}{1-y}~dy$$

If anyone has doubts about convergence, we have:

$$\lim_{t \to 0} \frac{H_t}{t} = \frac{\pi^2}{6}$$

Which would be another nice thing to prove, although I'm sure this proof is not hard to find.

It is also interesting that the related integral gives Euler-Mascheroni constant:

$$\int_0^1 H_t dt=\gamma$$

  • $\begingroup$ Wait a minute, your integral doesn't converge. $\endgroup$ – abnry Aug 28 '16 at 0:04
  • $\begingroup$ @abnry, Mahtematica computes it no problem $$\text{NIntegrate}\left[\frac{H_t}{t},\{t,0,1\}\right]$$ $\endgroup$ – Yuriy S Aug 28 '16 at 0:06
  • $\begingroup$ @abnry, Wolfram Alpha does too: wolframalpha.com/input/… $\endgroup$ – Yuriy S Aug 28 '16 at 0:09
  • $\begingroup$ whoops, my bad, I thought your $H_t$ was constant. $\endgroup$ – abnry Aug 28 '16 at 0:19

We apply $$ \frac{1-y^t}{1-y} = (1-y^t)(1+y+y^2+ \ldots)=(1-y^t)+y(1-y^t) +y^2(1-y^t)+\ldots $$ Each term gives after $y$-integration, $$ \frac t{t+1} + \frac{t}{2(t+2)}+ \frac t{3(t+3)} + \ldots $$ Then we divide these by $t$, $$ \frac 1{t+1} + \frac{1}{2(t+2)}+ \frac 1{3(t+3)} + \ldots $$ Taking integral with $t$ variable, we have the result.

Any interchange of integral and summation can be justified by Monotone Convergence Theorem.

  • $\begingroup$ That's nice and clear, thank you. If you want, look at my profile for more integrals equal to this series $\endgroup$ – Yuriy S Aug 28 '16 at 0:30
  • $\begingroup$ Thank you for letting me know. By the way, your limit $\pi^2/6$ also can be proved from my solution. $\endgroup$ – Sungjin Kim Aug 28 '16 at 0:33

Solution to the first part of this question was provided by @i707107.

For the second part, note that if we use the integral representation $H(t)=\int_0^1 \frac{1-y^t}{1-y}\,dy$, then we can write

$$\begin{align} \lim_{t\to 0} \frac{H(t)}{t}&=\lim_{t\to 0}\frac{\int_0^1 \frac{1-y^t}{1-y}\,dy}{t}\\\\ &=\lim_{t\to 0} \int_0^1 \frac{y^t \log(y)}{1-y}\,dy\\\\ &=-\int_0^1 \frac{\log(y)}{1-y}\,dy\\\\ &=-\int_0^1 \frac{\log(1-y)}{y}\,dy\\\\ &=\text{Li}_2(1)\\\\ &=\frac{\pi^2}{6} \end{align}$$

as was to be shown!

For the second part, we note that

$$\begin{align} \int_0^1 H(t)\,dt&=\int_0^1 \int_0^1 \frac{1-y^t}{1-y}\,dy\,dt\\\\ &=\int_0^1 \int_0^1 \sum_{n=0}^\infty (y^n-y^{n+t})\\\\ &=\sum_{n=0}^\infty \int_0^1 \left(\frac{1}{n+1}-\frac{1}{n+1+t}\right)\,dt\\\\ &=\sum_{n=0}^\infty \left(\frac{1}{n+1}-\log(n+2)+\log(n+1)\right)\\\\ &=\lim_{N\to \infty}\sum_{n=1}^N \left(\frac{1}{n}-\log(n+1)+\log(n)\right)\\\\ &=\lim_{N\to \infty}\left(\sum_{n=1}^N \frac1n -\log(N+1)\right)\\\\ &=\lim_{N\to \infty}\left(\sum_{n=1}^N \frac1n -\log(N)\right)\\\\ &=\gamma \end{align}$$

as was to be shown!

  • $\begingroup$ Please let me know how I can improve my answer. I really want to give you the best answer I can. -Mark $\endgroup$ – Mark Viola Sep 5 '16 at 21:08

$\newcommand{\angles}[1]{\left\langle\,{#1}\,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{\mathrm{i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\Li}[1]{\,\mathrm{Li}_{#1}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$

Note that

  • $\ds{ \sum_{k = 0}^{\infty}{1 \over \pars{k + \mu}\pars{k + \nu}} = {\Psi\pars{\mu} - \Psi\pars{\nu} \over \mu - \nu}\,,\qquad \pars{~\Psi:\ Digamma\ Function~}}$.
  • $\ds{H_{z} = \Psi\pars{z + 1} - \Psi\pars{1}}$.

1. \begin{align} \color{#f00}{\int_{0}^{1}{H_{t} \over t}\,\dd t} & = \int_{0}^{1}{\Psi\pars{t + 1} - \Psi\pars{1} \over t}\,\dd t\qquad\qquad \\[5mm] & = \int_{0}^{1}\sum_{k = 0}^{\infty}{1 \over \pars{k + 1}\pars{k + t + 1}}\,\dd t = \sum_{k = 0}^{\infty}{1 \over k + 1}\,\ln\pars{k + 2 \over k + 1} = \color{#f00}{\sum_{k = 1}^{\infty}{1 \over k}\,\ln\pars{1 + {1 \over k}}} \end{align}
2. \begin{align} \color{#f00}{\lim_{t \to 0}{H_{t} \over t}} & = \lim_{t \to 0}{\Psi\pars{t + 1} - \Psi\pars{1} \over t} = \lim_{t \to 0}\sum_{k = 0}^{\infty}{1 \over \pars{k + 1}\pars{k + t + 1}} = \sum_{k = 1}^{\infty}{1 \over k^{2}} = \color{#f00}{\pi^{2} \over 6} \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.